Ethics and Integrity in the Procurement of Goods and Services for the Military. (12th September 2017) - Fourie, David
Abstract : Public service ethics and integrity strengthen public trust and good governance, underpinning public servants' responsibility to exercise stewardship, and to use and develop all resources in the most economical, efficient, and effective way. Pure military procurement requires a sensitive procurement approach, subject to a regulatory system that acknowledges military confidentiality, striking a balance between openness and transparency in the military procurement process and protection of core security concerns of the procuring state. Ethics refers to established standards of right and wrong that prescribe what people ought to do, in relation to duties, principles, specific virtues, or benefits to society. For military staff as public administrators, ethics begins with and is grounded in duty. From an ethical perspective, there is a need for an overarching framework of moral values and ethical principles, which should have a significant and sustainable impact on the creation of public value as an outcome of military procurement processes. In the military procurement process, networks of deliberation and delivery in pursuit of public value require thoughtful and open-minded relationships with a commitment to a strong public service ethos. A sound ethical framework enables a public sector environment that encourages high standards of professional ethics and integrity in military procurement.